Ilmu Agama dan Ilmu Umum Dalam Sejarah Islam - NURAINI PANGARIBUAN (Sekolah Tinggi Agama Islam Program Studi Sejarah dan Kebudayaan Islam, 2024)
Islamic civilization reached its golden peak during the time of Bani Abbasiyah, Fatimiyah and up to Bani Umayyah, all of which were inseparable from the progress of science, because one of the indicators of the glory of Islamic civilization at that time was the high scientific activity. This research aims to describe the development of religious and general sciences in Islamic history from time to time. The method used in this research is the historical method or often called the historical method. The historical method is the process of critically analyzing and testing historical events based on the data owned. The results of this study indicate that the emergence and development of science in Islamic history experienced a significant phase, religious science first colored the lives of Muslim scientists, they were preoccupied with sciences based on the Qur'an and Hadith but after Islam expanded its territory (during the time of the great kingdoms) Muslim intellectuals then recognized the general sciences and developed them more broadly. So it can be interpreted that the rapid development of science is due to the strong enthusiasm of Muslim scientists to study religious science and develop general science that has been inherited by previous people. In addition, the concern of the rulers for science had a positive impact on the glory of Islamic civilization.